Neurobiological basis of Post-Traumatic Stress. - Coelho Rebelo Maia, Luis Alberto (Anales de Psicología / Annals of Psychology, 2010)
The Post-traumatic Stress Disorder (PTSD) has a long past but a short history (Saigh & Bremner, 1999; Serra, 2003). In Literature, pa-tients who suffer from pos-traumatic stress disorder are described as subjects that have been exposed to extremely stressful events, such as wars, natural disasters (floods and earthquakes), traffic accidents, rape, not only in childhood but also in adulthood. These patients, who undergo this disorder, suffer of intrusive memories and dissociation flashbacks related to the traumatic events in which they have very little or no control at all, nightmares, sleep disorders, hyper monitoring, exaggerated physiological reactions when remember traumatic events, avoiding reactions, emotional expression restriction, feelings of culpability and finally, a consequent social dysfunction (Bremner & Charney, 1994; Charney, Deutcg, Krystral, southwich & Davis, 1993; Bremner, Staib Kaloupek, Southwick, Soufer & Charney, 1999; Friedman & Yehuda, 1995). According to the exposed, several investigators felt necessity to deeply understand the Neurobiology of Post-Traumatic Stress Disorder. That subject, according to Bremner & Chaney (1994) and Friedman & Yehuda (1995) will allow us an ampler knowledge about the problem, being the propellant of the investigation advance of new treatments, essentially of Psychopharmacological nature. So, with the elaboration of this text, starting in an historical context of PTSD, we set out to produce a theoretical revision related to the different neurobiological mechanisms implied in PTSD, such as the psychopharma-cological indications at the moment of medical treatment.